2005
DOI: 10.1107/s0909049505011714
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of cellulose fibres and wood. Orientational aspectsin situinvestigated with synchrotron radiation

Abstract: Highly oriented native cellulose fibres (flax) and softwood (pine) have been investigated by means of X-ray diffraction. Local structural information was obtained by using X-ray microbeams. Tensile tests were performed in situ, revealing a change of orientation of cellulose microfibrils in materials with tensile strain. In flax fibres, the microfibrils rotate during the first percent of stretching, into a more parallel orientation with respect to the fibre axis. For wood, a decrease of orientation with the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 17 publications
(20 reference statements)
4
36
1
Order By: Relevance
“…However, the relationship between strain and f c observed for these highly oriented fibres (f c > 0.98) showed a slight deviation from linearity (Ko¨lln et al 2005).…”
Section: Resultsmentioning
confidence: 96%
“…However, the relationship between strain and f c observed for these highly oriented fibres (f c > 0.98) showed a slight deviation from linearity (Ko¨lln et al 2005).…”
Section: Resultsmentioning
confidence: 96%
“…Many advanced techniques have been used to follow the local micromechanics of natural cellulose fibres and composites, including Raman spectroscopy, synchrotron X-ray diffraction and half fringe photo-elasticity (Eichhorn et al 2001a, b;Kölln et al 2005;Martinschitz et al 2008;Hughes et al 2000). In this study however, the micromechanical deformation of coir and celery fibres will be investigated using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 97%
“…This difference between the two fibre types might be explained by the previous finding that the highly-processed Cottonized fibres have many more defects than the low-processed Green fibres [18] (see Figure 13), which possibly is caused by the stable growth of distributed damage. In other studies, it has been found that the microfibril angle is higher in defect regions than in non-defect regions [19][20][21], and this will lead to the hypothesis that more defective fibres will show more frequently a nonlinear stress-strain behaviour. This hypothesis is supported by the findings in the present study.…”
Section: Stress-strain Behaviourmentioning
confidence: 99%